The Effect of Self-Confidence, Adversity Quotient, and Self-Regulated Learning on Learning Motivation - Adela Tri Apriliyani; Weni Novandari; Ramita Kholifaturrohmah (Universitas Negeri Semarang, 2023)
This study aims to analyse: (1) The effect of self-confidence on learning motivation; (2) The effect of adversity quotient on learning motivation; and (3) The effect of self-regulated learning on learning motivation in economics subject for Class XI Social Sciences at Public High School 2 Purbalingga in the 2022 / 2023 academic year. The population in this study were all Class XI Social Sciences students at Public High School 2 Purbalingga for the 2022 / 2023 academic year. Sampling in this study used a proportionate stratified random sampling technique of 144 respondents. The data analysis technique used was multiple linear regression analysis with the SPSS version 23 program. The data collection method used questionnaires and interviews. Based on the results of research and data analysis, it can be concluded that self-confidence has a positive effect on learning motivation, adversity quotient has a positive effect on learning motivation, and self-regulated learning has a positive effect on learning motivation.